2018
DOI: 10.1007/s10549-018-4757-3
|View full text |Cite
|
Sign up to set email alerts
|

Circulating microRNAs from the miR-106a–363 cluster on chromosome X as novel diagnostic biomarkers for breast cancer

Abstract: PurposeNovel noninvasive biomarkers with high sensitivity and specificity for the diagnosis of breast cancer (BC) are urgently needed in clinics. The aim of this study was to explore whether miRNAs from the miR-106a–363 cluster can be detected in the circulation of BC patients and whether these miRNAs can serve as potential diagnostic biomarkers.MethodsThe expression of 12 miRNAs from the miR-106a–363 cluster was evaluated using qRT-PCR in 400 plasma samples (from 200 BC patients and 200 healthy controls (HCs)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
87
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 102 publications
(97 citation statements)
references
References 78 publications
(73 reference statements)
3
87
0
Order By: Relevance
“…Accumulative evidences indicate that a variety of miRNAs are involved in the regulation process of several tumors and play similar roles to tumor suppressor genes and oncogenes 22,23 The abnormal expressions of miR-21 and miR-205 are possibly related to the occurrence and development of breast cancer 12 Li et al 24 found that the miR-205 expression level is increased in epithelial ovarian cancer, and is closely related to the proliferation and invasion of ovarian cancer. In this study, we found that the level of miR-205-3p was significantly upregulated in breast cancer tissues, and further in vitro assay by overexpressing miR-205-3p validated its role on proliferation, invasion, and apoptosis of cancer cells, which was in line with previous findings 24 .…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Accumulative evidences indicate that a variety of miRNAs are involved in the regulation process of several tumors and play similar roles to tumor suppressor genes and oncogenes 22,23 The abnormal expressions of miR-21 and miR-205 are possibly related to the occurrence and development of breast cancer 12 Li et al 24 found that the miR-205 expression level is increased in epithelial ovarian cancer, and is closely related to the proliferation and invasion of ovarian cancer. In this study, we found that the level of miR-205-3p was significantly upregulated in breast cancer tissues, and further in vitro assay by overexpressing miR-205-3p validated its role on proliferation, invasion, and apoptosis of cancer cells, which was in line with previous findings 24 .…”
Section: Discussionsupporting
confidence: 91%
“…With the environmental deterioration and other factors, a younger trend of breast cancer occurrence has been shown in recent years20 The radical surgical resection, combined with radiotherapy and chemotherapy, marks the improvement regarding the survival time of early breast cancer patients, but its therapeutic effect is not satisfactory on advanced breast cancer patients 21 miRNA, as a kind of endogenous small noncoding RNA, plays an important role in cell differentiation, proliferation, and apoptosis through regulating the signaling pathway. In this study, we found that the level of miR-205-3p was significantly upregulated in breast cancer tissues, and further in vitro assay by overexpressing miR-205-3p validated its role on proliferation, invasion, and apoptosis of cancer cells, which was in line with previous findings24 .Our data showed that Ezrin and LaminA/C protein expressions in MCF-7 cells with miR-205-3p overexpression were significantly decreased compared with those in normal cells, which was consistent with previous finding 25 Ezrin protein is an important protein molecule in the ERM protein family, which, as a connexin between cytoskeleton and cell membrane, plays an important regulatory role in cell movement and adhesion, cytoskeletal remodeling, etc Ezrin protein also exerts important effects on the occurrence and metastasis of tumors26 It has been demonstrated that Ezrin functions as a prognostic factor and may predict potential lung metastasis in osteosarcoma and could also possibly be used as a new therapeutic target27 Ezrin is closely linked with the metastatic progression of cancer and is required in tumor-induced angio/lymphangiogenesis in vivo, which is frequently abnormally expressed in aggressive cancer types28 Interestingly, there is some controversy in the literature regarding the role of Ezrin in cancer metastasis and invasion. In this study, we found that the level of miR-205-3p was significantly upregulated in breast cancer tissues, and further in vitro assay by overexpressing miR-205-3p validated its role on proliferation, invasion, and apoptosis of cancer cells, which was in line with previous findings24 .Our data showed that Ezrin and LaminA/C protein expressions in MCF-7 cells with miR-205-3p overexpression were significantly decreased compared with those in normal cells, which was consistent with previous finding 25 Ezrin protein is an important protein molecule in the ERM protein family, which, as a connexin between cytoskeleton and cell membrane, plays an important regulatory role in cell movement and adhesion, cytoskeletal remodeling, etc Ezrin protein also exerts important effects on the occurrence and metastasis of tumors26 It has been demonstrated that Ezrin functions as a prognostic factor and may predict potential lung metastasis in osteosarcoma and could also possibly be used as a new therapeutic target27 Ezrin is closely linked with the metastatic progression of cancer and is required in tumor-induced angio/lymphangiogenesis in vivo, which is frequently abnormally expressed in aggressive cancer types28 Interestingly, there is some controversy in the literature regarding the role of Ezrin in cancer metastasis and invasion.…”
supporting
confidence: 91%
“…Two other members of the miR‐106‐363 cluster were enriched in HPV + OPSCC‐derived EVs, miR‐106a‐5p and miR‐20b‐5p/miR‐20b‐3p. miR‐106a‐5p and miR‐20b‐5p have recently been shown to be upregulated in breast cancer tissues and enriched in circulating serum EVs of breast cancer patients . miR‐20b‐5p has been described as a core HPV upregulated miRNA because it is consistently upregulated in HPV + OPSCC and cervical cancer tissues .…”
Section: Discussionmentioning
confidence: 99%
“…TSE are considered major drivers of PMN formation and critical mediators of cancer cell—immune cell communication. Measurements of exosomal miRNA have been shown to accurately reflect tumor progression, and may serve as a prognostic tool among several cancers, for example, nonsmall cell lung cancer, hepatocellular cancer, gastric cancer, urinary bladder cancer and gliomas …”
Section: Exosomes In Cancermentioning
confidence: 99%